Tannins in forage plants and their role in animal husbandry and environmental sustainability: a review. (6th May 2013) - Piluzza, G.; Sulas, L.; Bullitta, S.
Abstract The literature about tannins, polyphenolic secondary metabolites of plants, with both beneficial and adverse function according to their concentration and chemical structure, is vast and often conflicting. Tannins in forages have often been described as antinutritional factors, but this review aims to update information on beneficial effects on animals and the environment. Although research on the relation between tannins and animal production and health, for example, dry‐matter intake, digestibility, rumen fermentation and diseases, has mainly focused on condensed tannins, this review also discusses potential benefits from the use of hydrolysable tannins as a feed additive. Attention is given to the use of tannins in the mitigation of methane emissions from ruminants in forage‐based feeding systems and as a natural and ecologically friendly resource for improvement of nutrient utilization and environmental sustainability in meat and dairy farming.